Pengaruh Model Project Based Learning Berbantuan Media Virtual Terhadap Penguasaan Konsep Peserta didik pada Materi Alat-alat Optik - Ni Made Yeni Suranti; Gunawan Gunawan; Hairunnisyah Sahidu (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2016)
Learning physics should be able to provide an understanding physics of abstract concepts. One of the efforts being made to improve the learning of Physics is to use appropriate learning model. This study aims to improve the studentÃ¢â¬â¢s conceptual understanding by using project based learning model with virtual media for X Grade student at SMAN 2 Mataram Years 2015/2016. This study was conducted using a type of quasi-experimental research, untreated control group design with pretest and posttest on Optic. Hypothesis test results that the model used to give effect to theÃÂ  studentÃ¢â¬â¢s conceptual understanding, was shown to increase student conceptual understanding was higher in the experimental class compared with the control class. N-gain test results stating that the conceptual understanding has increased in each sub material. The results of the analysis conceptual understanding score on every aspect of cognitive increased.ÃÂ